Optimization of Bacillus cereus Fermentation Process for Selenium Enrichment as Organic Selenium Source - Chen, Xujun; Li, Shuyi; Cong, Xin; Yu, Tian; Zhu, Zhenzhou; Barba, Francisco J.; Marszalek, Krystian; Puchalski, Czesław; Cheng, Shuiyuan (Frontiers in Nutrition, 2020)
Selenium is an essential trace element and micronutrient for human health. Application of organic selenium in plants and microorganisms as trace element supplement is attracting more and more attention. In this study, Bacillus cereus, an important probiotic, was used for selenium enrichment with sodium selenite as selenium source. The growth curve of B. cereus was investigated, and 150 μg/ml was selected as the concentration of selenium for B. cereus fermentation. With application of response surface methodology, the optimal fermentation conditions were obtained as follows: inoculation quantity of 7%, culture temperature of 33°C, and shaking speed of 170 rpm, leading to the maximal selenium conversion ratio of 94.3 ± 0.2%. Field emission scanning electron microscope and energy dispersive spectrometry evidenced that inorganic selenium had been successfully transformed. This study may contribute to get a strain with high Se conversion ratio, so as to extract organic selenium in the form of selenoprotein to be used for further application.